PENGARUH KUALITAS PRODUK, SOCIAL MEDIA MARKETING,DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIANLAYANAN PREMIUM SPOTIFY - Fabian Cahaya Lesmana, (2022)
This study discusses The effect of Product Quality, Social Media Marketing, and Lifestyle on Purchase Decision. The purpose of this study was to determine the influence of Product Quality, Social Media Marketing, and Lifestyle on Purchase Decisions for Spotify Premium Services. The method used is quantitative. Data collection was carried out by distributing questionnaires. The population in this study were Spotify premium users in the Jabodetabek area, for the sample using the lemeshow formula which was then obtained as many as 100 respondents. The sampling technique used in this research is purposive sampling technique. The results of the study show that there is a positive and significant influence between product quality, social media marketing, and lifestyle on purchasing decisions. The conclusion from the study is that there is a fairly strong influence between product quality, social media marketing and lifestyle on purchasing decisions. The suggestion from this research is for Spotify to be able to develop other interesting features which of course the technology for listening to music will be more sophisticated from time to time in today's digital age. For this reason, Spotify must be able to continue to compete in the market with its latest innovations.